Prolonged viability of human organotypic skin explant in culture method (hOSEC) - Marco Andrey Cipriani Frade; Thiago Antônio Moretti de Andrade; Andréia Fernanda Carvalho Leone Aguiar; Flávia Araújo Guedes; Marcel Nani Leite; Williane Rodrigues Passos; Eduardo Barbosa Coelho; Pranab Kummar Das (Sociedade Brasileira de Dermatologia, 2015)
Abstract BACKGROUND: Currently, the cosmetic industry is overwhelmed in keeping up with the safety assessment of the increasing number of new products entering the market. To meet such demand, research centers have explored alternative methods to animal testing and also the large number of volunteers necessary for preclinical and clinical tests. OBJECTIVES: This work describes the human skin ex-vivo model (hOSEC: Human Organotypic Skin Explant Culture) as an alternative to test the effectiveness of cosmetics and demonstrate its viability through cutaneous keratinocytes' proliferative capacity up to 75 days in culture. METHODS: The skin explants obtained from surgeries were cultured in CO2-humid incubator. After 1, 7, 30 and 75 days in culture, skin fragments were harvested for analysis with histomorphological exam (HE staining) on all days of follow-up and immunohistochemistry for Ck5/6, Ck10 and Ki-67 only on the 75th day. RESULTS: On the 7th day, the epidermis was perfect in the dermoepidermal junction, showing the viability of the model. On the 30th day, the epidermis was thicker, with fewer layers on the stratum corneum, although the cutaneous structure was unaltered. On the 75th day, the skin became thinner but the dermoepidermal junctions were preserved and epidermal proliferation was maintained. After the 75th day on culture, the skin was similar to normal skin, expressing keratinocytes with Ck5/6 on supra-basal layers; Ck10 on differentiated layers; and viability could be assessed by the positivity of basal cells by Ki-67. CONCLUSION: The hOSEC model seems a good alternative to animal testing; it can be used as a preclinical test analogous to clinical human skin test with similar effectiveness and viability proven by immunohistological analyses.